The Attitude of Breastfeeding - Rulina Suradi; Suharyono Suharyono; Supardi Supardi; Hariarti Hariarti; W. A. F. J. Tumbelaka (Paediatrica Indonesiana, 1980)
A study of 211 mothers has been done at the Dr. Cipto Mangunkusumo General Hospital Jakarta and showed that more than half respectively 5I,9% in the low income group and 54,3% in the middle income group started feeding their babies not before 12 hours after birth and in the high income group 50,9% were fed after 24 hours. The number of mothers from all income group who breastfed has increased if we compare it to the condition before breastfeeding campaign one year before. The main reason to stop breastfeeding are in the middle and high income group due to willingness of the mother (the mother does not want to breast feed any more) because she has to work or due to the influence of advertisements. While in the low income group it is to the thought that after a certain time solid foods is enough for the baby. IUD is more popular amongst the low income mothers. This must be investigated more widely as to be used for breastfeeding campaign.